Inovasi Pengelolaan Wakaf Tunai Berbasis Integrasi Digital melalui Platform SatuWakaf.id - Riksa Zahra Kusdiani; Anisa Nurhidayah; Nanda Anissa Lestari; Rea Zaelanti; Aldi Syahdani Ikmatuloh; Andri Moewashi Idharul Haq (Jurnal Bisnis Inovatif dan Digital, 2026)
This article discusses innovations in cash waqf management through the integration of digital technology with the SatuWakaf.id platform developed by the Indonesian Waqf Board (BWI). The urgency of this research is driven by the need for a transformation in waqf governance to optimize the potential of the Sharia economy in the era of disruption. This study employs a literature review method with a qualitative approach to examine the role of digitalization in enhancing efficiency, transparency, and public participation in waqf. The findings indicate that digital waqf provides ease of access, transaction flexibility, and transparency through a real-time reporting system that is accountably accessible to donors (wakif). Furthermore, the integration of technologies such as QRIS, e-wallets, and internet-based systems effectively addresses various constraints of conventional waqf management, including limited reach and complex administration. However, significant challenges remain, such as low public literacy, limited technological competence among waqf managers (nazir), and cyber security risks surrounding digital transactions. Consequently, the optimization of digital waqf requires strong synergy between human resource development, adaptive regulatory strengthening, and the development of inclusive technological infrastructure to ensure that national waqf potential is fully utilized for the welfare of the community.